METHODOLOGICAL APPROACHES TO THE ASSESSMENT OF FUNCTIONING OF AGRICULTURAL CHAINS - Varchenko, O.O. (The actual problems of regional economy development, 2020)
The article is devoted to substantiation of methodical tools of research of efficiency of agro-food chains. The aim of the article is to generalize the existing methodological approaches to evaluating the effectiveness of agri-food chains, substantiation of the algorithm for determining value added at the micro and macro levels and components of information support. The following research methods were used: monographic; theoretical generalization, methods of cognition, dialectical method, analysis and synthesis, induction and deduction, systemic integrated approach. It is proved that the methodological basis for calculating the value added of global agri-food chains is the system of accounting for international trade based on value added Trade in Value Added and tables "Costs-Output", which are combined with national tables "Costs-Output". It is argued that it is difficult to calculate the value added of national origin, which is included in the intermediate costs of exported products. It is reasonable to study the directions of formation of value added of agro-food chains in the following directions: branches in the system of national accounts; by types of economic activity; at the level of business entities. It is proved that the calculation of value added in the study of agri-food chains should be carried out at the level of each participant (actor) in order to implement the principles of cost-oriented management and continuous determination of the value of this indicator at the level of economic entities. It is argued that in order to eliminate differences in the value of value added at the micro and macro levels, it is necessary to harmonize the financial statements of economic entities to the requirements of the SNA and provide for the allocation of value added on a separate line.